2013
DOI: 10.2135/cropsci2012.04.0218
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships in Zoysia Species and the Identification of Putative Interspecific Hybrids Using Simple Sequence Repeat Markers and Inflorescence Traits

Abstract: Z oysiagrass are warm-season, perennial turfgrass species that have high heat and drought tolerances, which generally reduces input and maintenance requirements. Due to their vigorous growth during the summer months, zoysiagrass are well adapted to the southern United States and upward into the transition zone. They are frequently used in residential lawns, golf courses, and landscapes. Due to their competitive drought tolerance and cold hardiness, zoysiagrass have been gaining in popularity throughout the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…According to previous studies, Z. matrella has intermediate morphological traits and overlapping geographical distribution with Z. japonica and Z. pacifica (Kitamura, 1967;Tanaka et al, 2015). Previous studies on genetic structure of Zoysia species distinguished Z. japonica and Z. pacifica but indicated that Z. matrella and interspecific hybrids had mixed alleles between these species (Kimball et al, 2013;Tanaka et al, 2015). Simple sequence repeat markers allowed detection of homozygous and heterozygous loci for each DNA sample (Paige, 2010) and have been used to identify genetic diversity among Zoysia species (Tsuruta et al, 2005;Mantia et al, 2011;Kimball et al, 2013;Tanaka et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…According to previous studies, Z. matrella has intermediate morphological traits and overlapping geographical distribution with Z. japonica and Z. pacifica (Kitamura, 1967;Tanaka et al, 2015). Previous studies on genetic structure of Zoysia species distinguished Z. japonica and Z. pacifica but indicated that Z. matrella and interspecific hybrids had mixed alleles between these species (Kimball et al, 2013;Tanaka et al, 2015). Simple sequence repeat markers allowed detection of homozygous and heterozygous loci for each DNA sample (Paige, 2010) and have been used to identify genetic diversity among Zoysia species (Tsuruta et al, 2005;Mantia et al, 2011;Kimball et al, 2013;Tanaka et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, winter tolerance decreased with decreasing of leaf width in zoysiagrass (Patton and Reicher, 2007). Simple sequence repeat markers allowed detection of homozygous and heterozygous loci for each DNA sample (Paige, 2010) and have been used to identify genetic diversity among Zoysia species (Tsuruta et al, 2005;Mantia et al, 2011;Kimball et al, 2013;Tanaka et al, 2016). According to previous studies, Z. matrella has intermediate morphological traits and overlapping geographical distribution with Z. japonica and Z. pacifica (Kitamura, 1967;Tanaka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular studies have confirmed this situation (Choi et al, 1997; Yaneshita et al, 1997; Weng et al, 2007; Bae et al, 2010; Kimball et al, 2012, 2013). There also appears to be a significant degree of more subtle introgression between species, which makes taxonomic distinctions more difficult: for example, plants nominally assigned to a particular species may be shown in molecular studies to be carrying some genetic material from another species (e.g., Kimball et al, 2013). When such plants are self‐pollinated and the progeny grown out as spaced plants, considerable morphological variation—hitherto unsuspected—can be revealed (D.S.…”
Section: Taxonomy and Originmentioning
confidence: 90%
“…Given the overlapping geographic distributions of the different Zoysia species, it is not surprising that there have also been reports of interspecific hybridization occurring naturally in the field (e.g., Ohwi, 1943;Nakamura, 1980;Fukuoka, 1989Fukuoka, , 2000Matumura et al, 1990;Choi et al, 1997;Chen and Phillips, 2006;Bae et al, 2010Bae et al, , 2013Lee et al, 2013). Recent molecular studies have confirmed this situation (Choi et al, 1997;Yaneshita et al, 1997;Weng et al, 2007;Bae et al, 2010;Kimball et al, 2012Kimball et al, , 2013. There also appears to be a significant degree of more subtle introgression between species, which makes taxonomic distinctions more difficult: for example, plants nominally assigned to a particular species may be shown in molecular studies to be carrying some genetic material from another species (e.g., Kimball et al, 2013).…”
Section: Hybridization Between Speciesmentioning
confidence: 99%